2019
DOI: 10.3390/jcm8122206
|View full text |Cite
|
Sign up to set email alerts
|

The Level of FGF 21 as a New Risk Factor for the Occurrence of Cardiometabolic Disorders amongst the Psoriatic Patients

Abstract: Fibroblast growth factors 21 and 23 are used as markers of cardiometabolic disorders which are common comorbidities in psoriasis. The study aimed to evaluate the serum level of these factors in psoriatic patients and elucidate the possible interplay between disease activity, metabolic or inflammatory parameters, and systemic treatment. A total of 33 patients with active plaque-type psoriasis and 11 healthy controls were enrolled in the study. Patients were divided into subgroups based on their BMI, disease sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…The available data on PON1 in psoriasis are conflicting. In the previous studies, its activity was reported to be lower than in the controls [12,18]. Therefore, patients with psoriasis were suggested to be considered at higher risk for atherosclerosis development [12].…”
Section: Discussionmentioning
confidence: 99%
“…The available data on PON1 in psoriasis are conflicting. In the previous studies, its activity was reported to be lower than in the controls [12,18]. Therefore, patients with psoriasis were suggested to be considered at higher risk for atherosclerosis development [12].…”
Section: Discussionmentioning
confidence: 99%
“…We were the first to evaluate the potential value of fibroblast growth factor 21 (FGF21) as one of the hepatokines in psoriasis. In a recently published paper, we concluded that FGF21 might be a novel predicting factor of CMD development in patients with psoriasis, especially with severe form or concomitant obesity [ 29 ]. These outcomes, together with significant roles in pathophysiological conditions, especially metabolic ones, prompt us to further explore the links with other hepatokines, particularly selenoprotein P. The biological function of SeP is characterized by the selenium transport, but it definitely has wider, unsuspected and still to be elucidated roles.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ACI decreased FGF-21 more than MTX. Finally, there was a positive link between FGF-23 and AST levels which suggests a possible link with liver activity [ 90 ] MTX Review of the evidence for the potential pro-atherosclerotic effects of MTX MTX improves endothelial function and vascular homeostasis, and is associated with a significant reduction in CV morbidity. These effects appear to be mediated via inhibition of pro-atherosclerotic cytokines such as TNF-α, IL-1 and IL-6 [ 91 , 92 ] CYC TGFβs plays a key role in cell growth and differentiation, modulation of immune activity and regulation of the cell cycle.…”
Section: Hepatic Effects Of Systemic Psoriasis Treatmentsmentioning
confidence: 99%
“…In one small trial, acitretin was reported to decrease FGF-21 by three-fold which was significantly greater than the reduction observed with methotrexate. 90 In an earlier small clinical trial, it was shown that patients with chronic psoriasis treated with acitretin had reduced retinol-binding protein-4 levels and decreased insulin resistance. 111 Given the link between psoriasis and increased insulin resistance/diabetes these changes could be clinically meaningful if confirmed in a larger study.…”
Section: Hepatic Effects Of Systemic Psoriasis Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation